Accounting for water and its role in achieving sustainability: An exploratory study on a sample of Samarra City Citizens - Hasan, Mustafa saeed (The Contrarian : Finance, Accounting, and Business Research, 2025)
This study examines the relationship between accounting for water quality and the achievement of environmental and financial sustainability in Samarra, amid declining government-provided water quality. Using a descriptive–analytical approach, data were collected via a five-point Likert scale questionnaire from 211 employees and faculty members at the University of Samarra. Results indicate a significant positive relationship between water quality and financial sustainability, and a weaker yet significant relationship with environmental sustainability. The findings demonstrate that poor government water quality imposes direct financial burdens on citizens and promotes unsustainable bottled water consumption. The study underscores the role of water accounting in assessing such impacts and recommends enhancing water infrastructure, integrating water accounting into environmental performance reporting, and providing temporary solutions to support citizens.